Navigating stormy waters - a case study on the effects of rising debts level on the container shipping industry - Bu, Roderick Chin Hearn (Nanyang Technological University, 2023)
This study seeks to identify the implications of increase in global debts on the Container shipping industry. With the dynamics and impacts of global debts affecting general businesses in mind, drawing relevant linkages to the current business environment of container shipping industry to reinforce the importance of financial resilience of container shipping especially since the last recession was more than a decade ago. There are a couple of studies pertaining to container shipping companies’ during the Great Financial Crisis (GFC). However, there is a lack of contemporary practices for container shipping. Secondly, due to a lack of literature with regards to financial resilience in the container shipping industry, a general business context will be explored prior looking into container shipping industry. Lastly, drawing a connection between general business context and container shipping context in terms of impact. Thirdly, lessons learnt from the past recession on container shipping to formulate relevant business strategies that shipping lines can adopt into their business strategies to remain adaptable and resilient to prepare for a looming recession and to serve as a reminder for companies to act prudently at every phase of the shipping market cycle.